2020
DOI: 10.1016/j.jsxm.2020.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Thiol/Disulfide Homeostasis in Patients with Erectile Dysfunction

Abstract: Background Although there are no sufficient data on association between oxidative stress and erectile dysfunction (ED), numerous studies have reported that imbalance between the formation of reactive oxygen species and body's antioxidant defenses may play a role in the pathogenesis of ED. Aim The aim of this study was to determine and compare the oxidant and antioxidant status in patients with ED and healthy controls with a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
2
1
0
Order By: Relevance
“…Micoogullari et al reported that thiol/ disulfide homeostasis is altered also in ED, and this may be a factor in its pathophysiology. Our study, in accordance with Micoogullari, shows that the thiol levels decreased in patients with ED (25).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Micoogullari et al reported that thiol/ disulfide homeostasis is altered also in ED, and this may be a factor in its pathophysiology. Our study, in accordance with Micoogullari, shows that the thiol levels decreased in patients with ED (25).…”
Section: Discussionsupporting
confidence: 92%
“…Some previous studies found decreased total thiol levels in patients with ED, which indicates that thiols may play a role in ED (25). However, in the literature, there were no studies on thiol levels in blood of corpus cavernosum in patients with ED and MetS.…”
Section: Discussionmentioning
confidence: 88%
“…In another word, thiol-disulfide homeostasis is reversible and in balance. This balance is disturbed in many illness situations (4,(25)(26)(27)(28). In our study, the decrease in native thiol level and increase in disulfide and % disulfide/ native thiol levels in MTX administired groups show that thiol-disulfide balance deteriorates in favor of oxidation (Table , Figure 3).…”
Section: Discussionsupporting
confidence: 47%